Shallow sounding (400MHz) radar profiles over three ice rises (Blåskimen Land, Kupol Ciolkovskogo and Kupol Moskovskij) in Western Dronning Maud Land - Goel, Vikram; Matsuoka, Kenichi (Norwegian Polar Institute, 2016)
This dataset consists of unprocessed radar profiles imaging upper 50~90 m of three ice rises, Blåskimen (four profiles), Kupol Ciolkovskogo (four profiles) and Kupol Moskovskij (three profiles), around the Fimbul Ice Shelf, western Dronning Maud land. Data also includes corresponding GPS locations along each profile. The scientific objective is to investigate the spatial and temporal variability in surface mass balance over this area. The data are provided in MATLAB (.mat) file format. Blaskimen: IRD_shallow_radar.mat Kupol Ciolkovskogo: IRB_shallow_radar.mat Kupol Moskovskij: IRC_shallow_radar.mat Each consisting struct-class variables for each profile as ‘Profile_1’, Profile_2’ etc. Profile_1 includes - - ‘dat’ matrix with radar amplitude data. - ‘twt’ array with two way travel time for the radar signal in seconds - ‘lat’ and ‘lon’ arrays with latitude and longitudes in decimal degrees - ‘x’ and ‘y’ arrays with coordinates in a polar stereographic projection parallel to 71° S (EPSG 3031)., and ‘z’ shows elevations above the WGS84 ellipsoid. All are in the unit of meters - ‘dist’ array with distance from the starting point in meters. Data were collected using GSSI SIR 3000 ground penetrating radar. See the following manuscript for further details: Goel, V., Brown, J., and Matsuoka, K.: Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica, The Cryosphere Discuss., https://doi.org/10.5194/tc-2017-61, in review, 2017.